High-fiber diet ameliorates gut microbiota, serum metabolism and emotional mood in type 2 diabetes patients - Chen, Lihua; Liu, Bo; Ren, Lixia; Du, Hao; Fei, Chunhua; Qian, Chang; Li, Bin; Zhang, Ruixia; Liu, Haixia; Li, Zongjie; Ma, Zhiyong (Frontiers in Cellular and Infection Microbiology, 2023)
Previous studies have demonstrated that patients with type 2 diabetes mellitus (T2DM) often had the problems of fecal microbiota dysbiosis, and were usually accompanied with psychiatric comorbidities (such as depression and anxiety). Here, we conducted a randomized clinical study to analyze the changes in gut microbiota, serum metabolism and emotional mood of patients with T2DM after consumption of a high-fiber diet. The glucose homeostasis of participants with T2DM was improved by the high-fiber diet, and the serum metabolome, systemic inflammation and psychiatric comorbidities were also altered. The increased abundances of Lactobacillus, Bifidobacterium and Akkermansias revealed that the proportions of beneficial gut microbes were enriched by the high-fiber diet, while the abundances of Desulfovibrio, Klebsiella and other opportunistic pathogens were decreased. Therefore, the current study demonstrated that the intestinal microbiota alterations which were influenced by the high-fiber diet could improve the serum metabolism and emotional mood of patients with T2DM.